Arctic Indigenous rights : the journey from Welfare State to Competition State - Alfa Dröfn Jóhannsdóttir 1983- (2014)
Læst til 14.6.2017 The race for resources in the Arctic plays a huge role in the rapid changes in the political, economic and cultural environment. Industrial development and the unfair manipulation of resources are having a direct impact on the traditional livelihoods of the Indigenous peoples. The rights of Arctic Indigenous peoples are being disregarded and the prospect of monetary payments connected to resource exploitation seems to control government actions in many ways. In addition, the welfare states seem to be slowly shifting towards the modern ways of competition states. Wellbeing, human rights and cultural heritage tend to score low on the spectrum of priorities vis-à-vis the horn of plenty, which has resulted in a scramble for natural resources or in some cases a race between states. Are states truly playing welfare games? In order to get a better grasp of the issues concerning the Arctic region, we must ask ourselves some pertinent questions such as: what rights do Indigenous populations have in all this? And what are the costs we are willing to pay in our endeavor to tap into their natural resources, both renewable and non-renewable? Perhaps it is time to take a look at the actions of the government to see if decisions concerning Arctic resources are based purely on economic growth of the few rather than the people’s wellbeing. Is the concept of a „competition state“ more immediate than initially though and are the Arctic people ready to comply with it? Kapphlaupið að auðlindum Norðurslóða spilar stórt hlutverk þegar kemur að breytingum á pólitísku, efnahagslegu og menningarlegu umhverfi svæðisins. Iðnþróun og ósanngjörn meðferð auðlindanna hafa bein áhrif á hefðbundið lífsviðurværi frumbyggja Norðurslóða. Réttindi þeirra frumbyggja eru sniðgengin og mögulegur efnahagslegur ágóði, tengdur nýtingu auðlindanna, virðist stjórna gjörðum stjórnvalda að mörgu leyti og velferðarríkið virðist vera að þróast hægt yfir í samkeppnisríki nútímans. Vellíðan, réttindi og menningarleg arfleifð virðist vera ...